Farmers’ Perceptions and Drivers of Antimicrobial (2020)
Antimicrobial resistance (AMR) in humans has been linked to non-judicious antimicrobial use (AMU) in food animals. To develop antimicrobial stewardship plans (AMSPs) for pig farmers, there is the need to understand the current status of AMU and the driving factors in the industry. Data on AMU, farmers’ perceptions of associated drivers, and biosecurity were collected through a mixed-method study design with focus group discussions (FGDs) and questionnaire-based interviews. Antimicrobials (AMs) were mainly used for therapeutic and prophylactic purposes. Common AMs used were tetracycline (78.8%), gentamycin (53.8%), and tylosin (52.5%). Perceived drivers of AMU were linked to economic benefits, farmers’ previous experiences, sick animals, expensive veterinary services, easy accessibility to over-the-counter drugs, poor farm practices, and poor disease prevention strategies. AMU was poor (average 40.2%), while knowledge on AMs and implications for animal and human health was considered averagely satisfactory (56.4%). The biosecurity level was also satisfactory (53.0%) and significantly associated with having a written farm health plan (p = 0.035). Good AMU was found to be strongly associated with farmers’ use of veterinary services (p = 0.001). Diverse factors drive antimicrobial use among pig farmers in Ogun State, and these could be addressed by providing continuing education on antimicrobial stewardship and best farm practices.